THE MYTH OF “EASY” IN CARRIER PERCEPTION OF CHILDREN WITH DIARRHEA IN THE CENTRAL ICU PICU ROOM JOMBANG REGENCY HOSPITAL - Andi Yudianto; Sumarti Sumarti; Muhammad Rajin; M. Zahrul Azhar (Bajang Institute, 2022)
There are many myths about disease among the people that are believed to be true for generations. One of myth in children with diarrhea is a “ enteng entengi” myth. “Enteng-Entengi” is myth from java that believes that diarrhea in children is a sign of increasing growth and development skills. This myth has an impact on delays in making decisions to bring children with diarrhea to health service facilities. The purpose of this study was to understand caregivers' perceptions of the